(untitled) (Research, Society and Development, 2019)
The National Parks constitute as Units of Conservation fundamental for the conservation of the biodiversity. However, the public visitation in these places generates, among other problems, increased environmental degradation. In order to avoid this impact, the managers of these areas need to create mechanisms capable of handling the visitation and, consequently, to avoid any negative impact in those places. In this sense, this study aimed to analyze the profile of the visitors of the Tijuca National Park, Rio de Janeiro. Online questionnaires were applied during the period from January to April 2018. As a result, the data indicate that individuals who go to the NTP are satisfied with the attractions and the experience of the visit, but they claim for more dissemination, security and infrastructure within. of the park. There is also optimism about the potential of NTP visitation, but it would be necessary to invest in recreation, leisure and environmental education. In view of this, it was observed that the effectiveness of PNT visitation management needs to be based on the public interest, which recognizes the importance of the park in its different aspects, as well as agree that lack of conditions, most of them public order, to be able to contemplate even more this natural space.